2009
DOI: 10.1021/om900656t
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of the Transition States and Products of Methyl Radical Addition to Olefins Coordinated in an Asymmetrical Mode to [Cp2Zr(OtBu)]+: Predictions of Reversed Regioselectivities Compared to the Noncoordinated Reactions

Abstract: The addition of free alkyl radicals to olefins is known to encounter a small activation energy and to be highly regioselective, typically favoring the less substituted carbon of the double bond. The ability to modify the reactivity and regioselectivity of the given reaction can be of interest from both fundamental and practical perspectives. Olefins are known to bind to the [d 0 -Cp 2 Zr(O t Bu)] þ fragment (Zr) relatively weakly, affording adducts having a nonclassical asymmetrical bond between Zr and the dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…This should be associated with an energetic cost, which is greater in the case of a trans -coordinated Ni–P bond, and contributes further toward a larger barrier in 2a-C 2 H 4 . Related effects of the ancillary ligands have been invoked to account for calculated large differences in the activation energies of alkyl to CO migratory insertion in isomeric octahedral complexes. , Also, previous experimental , and theoretical , studies have shown that asymmetric metal–olefin coordination polarizes the π-electron density of the olefin toward the metal center, presumably accounting for the high trans influence resulting from this coordination mode.…”
Section: Resultsmentioning
confidence: 99%
“…This should be associated with an energetic cost, which is greater in the case of a trans -coordinated Ni–P bond, and contributes further toward a larger barrier in 2a-C 2 H 4 . Related effects of the ancillary ligands have been invoked to account for calculated large differences in the activation energies of alkyl to CO migratory insertion in isomeric octahedral complexes. , Also, previous experimental , and theoretical , studies have shown that asymmetric metal–olefin coordination polarizes the π-electron density of the olefin toward the metal center, presumably accounting for the high trans influence resulting from this coordination mode.…”
Section: Resultsmentioning
confidence: 99%